Athen, Griechenland. Forschungen im Rahmen des Projektes »Shapes of Ancient Greece«: Das Fragment einer spätgeometrischen Riesenamphora. Arbeiten im Jahr 2022 - Ruppenstein, Florian (e-Forschungsberichte des DAI, 2022)
A fragment of a giant vessel dating to the Late Geometric period (c. 750 BC) with two partly preserved mourners from the margin of a prothesis or ekphora scene is kept in the archaeological collection of the German Archaeological Institute at Athens. It is demonstrated that the fragment formed part of a belly-handled amphora that was manufactured in the Dipylon workshop. The sherd was found in Athens in the area of the railway line slightly west of Theseion station. Therefore, the amphora fragment bears witness to the existence of an otherwise unknown high status burial place next to the cemeteries in the Kerameikos and the Agora area that was probably destroyed during construction of the railway.